Water Level Monitoring System - Nazri, Muhammad Najmi Zikry; Abd Shaib, Mohd Fadzli (Evolution in Electrical and Electronic Engineering, 2021)
This paper focusing on implement a water level monitoring system that is used for water tanks in agricultural facilities to perform crop watering activities. This will improve monitoring of water level in water tank if this sector facing a water crisis such as water supply cut off. This will help the farmers to prepare the next step with help water level monitoring system that gives accurate water quantity in water tank or storage. Water Level Monitoring System is helpful to the farmers knowing the actual amount of water in the water tank for agricultural usage. Bylnk application as the Internet of things (IoT) platform that will give all the information about the water level and monitoring the activities of water consumption at a certain time. Hence, from the findings of the study, the water level monitoring system is successfully developed according to monitor the water level in the water tank. Based on the result analysis shows the Water Level Monitoring System is capable of monitoring water level and also the Blynk application successfully displays the water level and notifies if the water level is at lower condition.